A dual mortar embedded mesh method for internal interface problems with strong discontinuities. (5th August 2022) - Ao, Jun; Zhou, Mozhen; Zhang, Bingyin
Abstract: Internal interface problems with strong discontinuities for inclusion‐matrix systems are common and also challenging in engineering. In this work, a dual mortar embedded mesh method is proposed. An XFEM (extended finite element method) model is used for the underlying matrix, which can then be meshed without considering internal boundaries. The inclusions are treated by conventional FEM (finite element method) model. The FEM‐XFEM coupling is treated by the dual mortar method, which uses the XFEM side to carry the Lagrange multiplier for imposing inclusion‐matrix contact constraints. The present method is first validated by contact patch tests as well as bending tests and then applied to simulate strong discontinuities arising from bolt‐rock and pile‐soil interactions. The numerical results indicate that the present method is capable of simulating the internal interface problems with high accuracy, computational efficiency as well as mesh convenience.